Towards an organizational perspective on party funding: explaining financial transfers from MEPs to their national parties - Bolleyer, Nicole; Trumm, Siim; Banducci, Susan A. (Wiley, 2012)
Which European Parliament (EP) parties are able to extract regular donations from their MEPs' salaries and if they extract donations how great are they? In the literature on party finances, there has been a lack of attention paid to the use of salaries of elected representatives as a source of funding. This is surprising given that the national headquarters of many parties in Europe regularly collect 'party taxes': a fixed (and often significant) share of their elected representatives' salaries. In filling this gap, we theoretically specify two sets of party characteristics that account for the presence of a taxing rule and the level of the tax respectively. The presence of a tax depends on the basic ‘acceptability’ of such an internal obligation that rests on a mutually beneficial financial exchange between parties’ campaign finance contributions to their MEPs and MEPs’ salary donations to their parties. The level of the tax, in contrast, depends on the level of intra-organisational compliance costs and parties’ capacity to cope with these costs. Three factors are relevant to this second stage: MEPs’ ideological position, the size of the parliamentary group and party control over candidate nomination. Our framework is tested through a selection model applied to a unique dataset covering the taxing practices in parties across the EU member states.